Pseudo-Complex General Relativity 2015
DOI: 10.1007/978-3-319-25061-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-complex General Relativity

Abstract: An extension of the theory of General Relativity is proposed, based on pseudo-complex space-time coordinates. The new theory corresponds to the introduction of two, in general different, metrics which are connected through specific conditions. A pseudo-complex Schwarzschild solution is constructed, which does not suffer any more by a singularity. The solution indicates a minimal radius for a heavy mass object. Consequences for the redshift and possible signatures for its observation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 32 publications
0
67
0
Order By: Relevance
“…The new metric component g 00 , proposed in this contribution, is of the form 12m0r+fr, where f ( r ) comes off stronger than 1/ r 2 . Such a term was also proposed in Hess et al (), within the pseudo‐complex General Relativity (pcGR) Hess & Greiner ().…”
Section: Introductionmentioning
confidence: 88%
“…The new metric component g 00 , proposed in this contribution, is of the form 12m0r+fr, where f ( r ) comes off stronger than 1/ r 2 . Such a term was also proposed in Hess et al (), within the pseudo‐complex General Relativity (pcGR) Hess & Greiner ().…”
Section: Introductionmentioning
confidence: 88%
“…The orbital frequency for a particle in a circular orbit and for n = 3 was given in Schönenbach (2013); Hess (2015). For n arbitrary and for prograde orbitals, this is…”
Section: The Theory Consequences and Predictionsmentioning
confidence: 99%
“…The orbital frequency of a particle in a circular orbit for the case GR (upper curve) and for n = 3 (dashed curve) and n = 4 (dotted curve) B = B max . constant (it is a function in r, see also Hess (2015)). In Schönenbach (2014) it is shown that for a 0.4 m (n = 3) the last stable orbit is at a lower value of r but follows approximately the behavior of GR.…”
Section: The Theory Consequences and Predictionsmentioning
confidence: 99%
“…The general avoidance of spacetime singularities would be a desirable feature, for example, in a future quantum theory of gravity (Penrose ). Due to the lack of a fully quantized theory of gravity, pseudo‐complex GR (pc‐GR) represents an alternative approach by postulating that no acceptable physical theory should present singularities (Hess & Greiner ).…”
Section: Pseudocomplex General Relativitymentioning
confidence: 99%
“…Conceptually speaking, in pc‐GR, mass not only curves spacetime but is supposed to also be able to change vacuum properties of the universe. This theory has been applied, among other systems, to neutron stars (Hess & Greiner ).…”
Section: Pseudocomplex General Relativitymentioning
confidence: 99%